Utilization of asphalt waste Dust and fly ash for sustainable mortar - Ayawanna Jiratchaya; Kingnoi Namthip; Sertsoongnern Pimchanok; Chaiyaput Salisa (E3S Web of Conferences)
This study presents a utilization of asphalt waste dust (AD) as a filler material to replace sand in a mortar. Moreover, fly ash (FA) is utilized as an additive of pozzolanic material. The compressive strength and microstructures were investigated to propose the suitable ratio of AD and FA for sustainable mortar. All samples were fixed with a mixing ratio of ordinary Portland cement (CM): sand (Si) at 1: 2.75. The Si was replaced by AD content at 0, 50, 60, 70, 80, 90, and 100% by weight (%wt) of Si, respectively. Furthermore, the FA was added to the suitable mixing conditions of CM, AD, and Si, which is called the suitable mortar containing AD, at 0, 10, 20, 30, and 40 %wt. The results from the compressive strength test were evaluated and compared under the different curing times for 3, 7, and 28 days in saturated limewater. The microstructures of testing samples were analyzed using different characterization techniques including X-ray diffraction (XRD) and scanning electron microscopy (SEM) with energy-dispersive X-ray spectroscopy (SEM-EDS). From the results, the mortar containing AD showed higher compressive strength than those without AD. After the addition of FA and AD, the compressive strength was more increased rather than using AD without FA. Sand can be replaced with AD as filler aggregates to reduce voids in the mortar. Additionally, FA can be used as a pozzolanic additive in mortars. Therefore, those two waste materials (AD and FA) are alternative materials suitable for use in the development of compressive strength in mortar.